Pemeriksaan Profil Asam Urat Sebagai Cerminan Risiko Gangguan Metabolik Di Kelurahan Tanjung Duren Selatan - Gunawan, Paskalis Andrew; Santoso, Alexander Halim; Destra, Edwin; Philo, Andrew; Mahendri, Ryan Daffano Putra (Universitas 17 Agustus 1945 Semarang, 2025)
Hyperuricemia contributes to various metabolic disorders, including gout and kidney disease. Detection of uric acid levels through simple screening is important for early risk identification. One non-pharmacological approach that can help reduce uric acid levels is maintaining adequate fluid intake. Uric acid level examination was performed by taking capillary blood from 104 adult participants. Results were obtained directly using the Point-of-Care Testing (POCT) instrument. Education was provided to all participants using a leaflet discussing the role of hydration in supporting uric acid excretion. The average uric acid level was recorded at 4.08 ± 1.00 mg/dL. A total of 103 participants (99.0%) were in the normal range, and 1 participant (1.0%) had high levels. Most participants have not experienced excessive urate accumulation, but still need education to maintain this status. Uric acid level screening is useful as an effort to detect the risk of metabolic disorders early. Education about the importance of fluid intake is the main strategy to maintain uric acid levels within normal limits and prevent complications due to hyperuricemia.